Transcatheter closure of perimembranous ventricular septal defects (VSDs) using the Amplatzer duct occluder I device. (September 2017) - Sobhy, R.; El-Sisi, A; Fattouh, AM; Agha, HM; El-Saiedi, SA; Attia, W; Abdelaziz, DM; Hamza, H
Highlights: Perimembranous VSDs in symptomatic infants and children need to be closed. Amplatzer ductal occluder I is safe and effective for closure of pmVSDs. The antegrade venous approach is feasible reducing the fluoroscopic time.